Numerical Study of Biomass Grate Boiler with Coupled Time-Dependent Fuel Bed Model and Computational Fluid Dynamics Based Freeboard Model - Zhou, Anqi; Xu, Hongpeng; Yang, Wenming; Tu, Yaojie; Xu, Mingchen; Yu, Wenbin; Boon, Siah Keng; Subbaiah, Prabakaran (Energy & fuels, 2018)
In this paper, a coupled numerical model is developed to provide an advanced simulation for industrial scale grate boilers. The detailed process of biomass conversion in the grate bed is captured using the developed one-dimensional fuel bed model, taking into consideration the separately controlled residence time and primary air supply in different zones. The distributions of gas concentrations, temperature, and bed height along the grate bed are described by the transient simulation results, which are then coupled to the three-dimensional freeboard simulation model as boundary conditions. The results from the coupled model are compared with the on-site measurement data from a wood-chip grate boiler for steam generation, and good agreements are achieved. The in-furnace combustion processes for different quality fuels are evaluated using the model. The results show that higher quality fuel has a larger high temperature combustion zone together with a lower bottom ash temperature, which suggests a higher efficiency. Moreover, a comparison between the standard grate speed control scheme and the modified one shows that increasing the fuel residence time in the first zone has the potential for improving the boiler’s combustion efficiency.